Catecholaminergic polymorphic ventricular tachycardia: An exciting new era - Behere, Shashank P (Ann Pediatr Cardiol, 2016)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a highly malignant inheritable cardiac channelopathy. The past decade and a half has provided exciting new discoveries elucidating the genetic etiology and pathophysiology of CPVT. This review of the current literature on CPVT aims to summarize the state of the art in our understanding of the genetic etiology and the molecular pathogenesis of CPVT, and how these relate to our current approach to diagnosis and management. We will also shed light on groundbreaking new work that will continue to refine the management of CPVT in the future. As our knowledge of CPVT continues to grow, further studies will yield a better understanding of the efficacy and pitfalls of established diagnostic approaches and therapies as well as help shape newer diagnostic and treatment strategies. Two separate searches were run on the National Center for Biotechnology Information's (NCBI) website. The first used the medical subject headings (MeSH) database using the term “catecholaminergic polymorphic ventricular tachycardia” that was run on the PubMed database using the age filter (birth to 18 years), and it yielded 58 results. The second search using the MeSH database with the search term “catecholaminergic polymorphic ventricular tachycardia,” applying no filters yielded 178 results. The abstracts of all these articles were studied and the articles were categorized and organized. Articles of relevance were read in full. As and where applicable, relevant references and citations from the primary articles were further explored and read in full.